Inclusão digital - Parreira, Arthur Mortari [UNESP]; Okida, Estela Silva [UNESP]; Perticarrari, Amanda Lins Pacífico Manfrim [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This Project aims to contribute to the digital inclusion of the population of Jaboticabal / SP, where is locate the Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP – FCAV). The target audience is students from public schools in the city, and we aim to acquaint, motivate and prepare them for meaningful use of computers and the internet. In addition to reflecting on the impact of these Technologies in a several aspects of life, society and their teaching, promoting digital education for this population’s group and make them able to enter at the labor market.

Esse projeto visou à inclusão digital da população de Jaboticabal/SP, onde se localiza a Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP – FCAV). O público interessado foram os alunos de escolas públicas do município; este projeto buscou familiarizá-los, motivá-los e prepará-los para a utilização significativa de recursos de computadores e da internet. Além de refletir sobre o impacto dessas tecnologias nos diversos aspectos da vida, da sociedade e de sua prática pedagógica, proporcionando uma educação digital para esse grupo da população e tornando- os capaz de ingressar no mercado de trabalho.
Keywords: Digital inclusion; Informatization; Inclusão digital; Informatização